Penerapan Jaringan Syaraf Tiruan Dengan Metode Backpropagation Untuk Memprediksi Penjualan Sepeda Motor Yamaha Di Asli Motor Siantar - Muhammad Fajar; Sumarno Sumarno; Indra Gunawan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2021)
The research was conducted at CV. ORIGINAL SIANTAR MOTORS that have a problem, namely the lack of sales is a very bad thing for the CV because it results in the economy and the turnover of motorbike sales capital is not good. This problem can be overcome by using the Backpropagation method which is usually used by multilayer networks to minimize errors in the output by testing data using Matlab 6.1. The purpose of this research is expected that using this method can increase the number of sales of motorbikes in each type, and increase the economic income for employees who work at the CV in the form of bonuses. The results of this study are to estimate the highest type of motorcycle sales in 2020 using sales data for 2017, 2018 and 2019.